2013
DOI: 10.1097/prs.0b013e3182879f4a
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pressure and Shear on Autologous Fat Grafting

Abstract: Higher aspiration pressures up to -0.83 atm did not affect fat graft viability in vivo. Positive pressure up to 6 atm also did not affect fat graft viability. The degree of shear stress, which is a function of flow rate, did significantly affect fat graft viability. Fat grafts injected slowly with low shear stress significantly outperformed fat injected with high shear stress. These data suggest that shear stress is a more important variable regarding fat graft viability than pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(69 citation statements)
references
References 21 publications
1
68
0
Order By: Relevance
“…[81][82][83] Similarly, no differences have been seen in animal studies of ultrasound-assisted harvest. 84 No significant human or animal trials exist for mechanical or laser-assisted liposuction, but in vitro studies have revealed a lower stem cell yield and poorer ASC proliferation.…”
Section: Emerging Strategiesmentioning
confidence: 88%
“…[81][82][83] Similarly, no differences have been seen in animal studies of ultrasound-assisted harvest. 84 No significant human or animal trials exist for mechanical or laser-assisted liposuction, but in vitro studies have revealed a lower stem cell yield and poorer ASC proliferation.…”
Section: Emerging Strategiesmentioning
confidence: 88%
“…In a murine model, it was shown that the application of positive pressure alone, in contrast to shear stress, did not significantly alter the graft volume or the histology after 4 weeks in vivo. 16 The application of shear stress on fat tissue, by injecting adipose tissue through a 3-cc syringe with a 16-gauge angiocatheter, led to lower yields of graft volume at explantation.…”
Section: Discussionmentioning
confidence: 99%
“…7 One of the most thorough studies investigating fat grafting unfortunately omitted the unique chance of linking in vitro analysis of stromal vascular fraction with the clinical outcome of fat graft volume. 16 The mechanical forces applied when shuffling harvested adipose tissue through a small-diameter three-way stopcock are a combination of positive pressure (defined as supra-atmospheric pressure) and shear stress. In a murine model, it was shown that the application of positive pressure alone, in contrast to shear stress, did not significantly alter the graft volume or the histology after 4 weeks in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Lee et al's May 2013 study, "The Effect of Pressure and Shear on Autologous Fat Grafting," it was found that pressure and shear are the two main, important variables determining fat graft survival. 1 Higher aspiration pressures up to −0.83 atm did not affect fat graft viability in vivo. We congratulate Lee's team on their efforts to systematically study the impact of these physical processing variables on fat harvest; however, we have some concerns about the evaluation methods used to study fat graft survival.…”
mentioning
confidence: 94%